Improving the Study of Social Representations through Word Associations: Validation of Semantic Contextualization. Issue 4 (November 2018) - Piermattéo, Anthony; Tavani, Jean-Louis; Monaco, Grégory Lo
To grasp how individuals and groups perceive social objects of their environment, word association tasks enable the cognitions associated with a given object to be collected. However, the lack of information regarding the meaning of these responses implies interpretation and subjectivity in their analysis. To reduce this subjectivity, this research aims to validate semantic contextualization (SC), a procedure that allows participants to explain the link they establish between their response and the object under study. In an experimental study, we asked 94 undergraduate students to categorize the results of word association tasks, having available or not the responses resulting from the SC task. We observed that SC improved categorization at different levels such as perception of the difficulty of the task, agreement between participants, uncertainty, and homogeneity of the categorization. These results lead us to consider this method a useful addition to word association tasks.